Chemical Characterization, Antioxidant, Cytotoxic and Microbiological Activities of the Essential Oil of Leaf of Tithonia Diversifolia (Hemsl) A. Gray (Asteraceae) - Ana Luzia Ferreira Farias; Alex Bruno Lobato Rodrigues; Rosany Lopes Martins; Érica de Menezes Rabelo; Carlos Wagner Ferreira Farias; Sheylla Susan Moreira da Silva de Almeida (MDPI AG, 2019)
The present study aimed to evaluate the chemical composition, antioxidant potential, and the cytotoxic and antimicrobial activity of the essential oil of the plant species Tithonia diversifolia (Hemsl) A. Gray. The essential oil obtained was used to identify the chemical compounds present through the techniques of GC-MS and NMR. The antioxidant potential was calculated by the sequestration method of 2,2-diphenyl-1-picrylhydrazyl. For cytotoxic activity, the larval mortality of Artemia salina was evaluated. The main chemical constituents identified are αpinene (9.9%), Limonene (5.40%), (Z)-β-ocimene (4.02%), p-cymen-8-ol (3.0%), Piperitone (11.72%), (E)-nerolidol (3.78%) and Spathulenol (10.8%). In the evaluation of the antimicrobial activity, bacterial strains of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were used. The results showed that the bacterium E. coli were more susceptible to the presence of the essential oil, presenting minimal inhibitory concentration at the concentrations that were exposed. The essential oil presented antioxidant activity of 54.6% at the concentration of 5 mg·mL−1 and provided a CI50 of 4.30. It was observed that the essential oil of this species was highly toxic against A. salina lavas, as its cytotoxic activity showed an LC50 of 3.11. Thus, it is concluded that T. diversifolia oils are effective in inhibiting bacterial growth and reducing oxidative stress.